The Palgrave Handbook of State-Sponsored History After 1945
XXV, 877 p. 17 illus., 8 illus. in color.
Keywords: This handbook provides the first systematic integrated analysis of the role that states or state actors play in the construction of history and public memory after 1945. The book focuses on many different forms of state-sponsored history, including memory laws, monuments and memorials, state-archives, science policies, history in schools, truth commissions, historical expert commissions, the use of history in courts and tribunals etc. The handbook contributes to the study of history and public memory by combining elements of state-focused research in separate fields of study. By looking at the state’s memorialising capacities the book introduces an analytical perspective that is not often found in classical studies of the state. The handbook has a broad geographical focus and analyses cases from different regions around the world. The volume mainly tackles democratic contexts, although dictatorial regimes are not excluded. .